Biocompatible and Nanoenabled Technologies for Biological Modulation. Issue 2 (18th June 2021) - Ostroff, Eleanor; Parekh, Kavita; Prominski, Aleksander; Tian, Bozhi
Abstract: Biocompatible and nanoscale devices for biological modulation of cells and tissues possess the potential for tremendous impact on medical and industrial technologies. Typical medical devices and therapies tend to be macroscale, comprised of nonbiocompatible materials, and broadly targeted, resulting in imprecise treatments and adverse effects such as chronic immune response and tissue damage. The development of nanoenabled and biocompatible technologies—ranging from biodegradable nanoparticles for localized drug delivery to transient electronic devices for stimulation therapy to engineered biofilms with applications to nanomedicine—will continue to enable the advent of personalized medicine and precision therapies. In this review, recent research into this frontier is reviewed, first analyzing the synthesis of nanoenabled and biocompatible technologies and then presenting significant considerations regarding the development of such materials. Lastly, the latest advancements in biocompatible, nanoenabled devices are examined, followed by a discussion of the direction of future research in the field. Abstract : Nanoscale devices can benefit the development of medical technologies with efficient and biocompatible solutions for precise and personalized treatments. Such a high precision of nanoenabled solution allows minimizing immune responses and tissue damage compared to traditional approaches. This review summarizes the newest developments and opportunities in the field of nanoscaled bioelectronics.